Seguro garantia: performance bond nos contratos de construção do setor privado - Rodrigues, Natália Bastos de Sá (2023)
This thesis proposes to gather and analyze the bibliography, documents, information, and standards available regarding surety bond to enable a better understanding of the subject, which is little explored in Brazilian legal doctrine. Surety bond is a very important instrument, commonly used to minimize the uncertainties that affect infrastructure projects, ensuring compliance with contractual obligations assumed. Thus, this work will present the fundamentals of surety bond, providing the general notions of definition and classification of the institute, in addition to distinguishing it from insurance and suretyship, to expose the discussion regarding its legal nature, allowing the identification of the legal regime applicable, concluding that the institute is subject to current insurance rules and procedures established by SUSEP. The next step will contextualize its historical-evolutionary origin and bring together the sources of Brazilian law applicable to it, including the analysis of the most recent of them, Circular SUSEP nº 662/2022, which came in effect in 2022. This thesis will also explain the relationships between the policyholder, the insured and the insurer within the scope of their respective instruments, namely, the main contract, the counter-guarantee constitution contract, and the policy, in addition to introducing surety bond modalities to guarantee the obligations contained in the main construction contracts. Afterwards, it will deal specifically with the performance bond modality in private sector construction contracts, addressing specific aspects of the indemnifiable damage and the coverage of contractual penalties, passing through the indemnity principle and the contractual limitations to the duty to indemnify. Finally, it will analyze the supposed “contractual freedom” intended by SUSEP with the new Rule, concluding that this should not be understood as parity between the parties in the scope of the legal transaction, but as the freedom to innovate by the insurer itself to create new products insurance policies and a certain flexibility in adapting policies, which limits will be explored in this paper